Severe hypermagnesemia presenting with abnormal electrocardiographic findings similar to those of hyperkalemia in a child undergoing peritoneal dialysis - Won Kyoung Jhang; Yoon Jung Lee; Young A Kim; Seong Jong Park; Young Seo Park (Korean Pediatric Society, 2013)
In this report, we present a pediatric case of severe symptomatic hypermagnesemia resulting from the use of magnesium oxide as a laxative in a child undergoing continuous cyclic peritoneal dialysis for end-stage renal disease. The patient showed abnormal electrocardiography (ECG) findings, such as tall T waves, a widened QRS complex, and irregular conduction, which were initially misdiagnosed as hyperkalemia; later, the correct diagnosis of hypermagnesemia was obtained. Emergent hemodialysis successfully returned the serum magnesium concentration to normal without complications. When abnormal ECG changes are detected in patients with renal failure, hypermagnesemia should be considered.